Application of optical coherence tomography in neurodegenerative diseases: a focus on Parkinson’s, Alzheimer’s, and Schizophrenia in Bulgarian patients - Alina Y. Levi; Sylvia Cherninkova; Vihra Milanova; Vasil M. Haykin; Alexander H. Oscar (Biotechnology & Biotechnological Equipment)
This study investigates retinal alterations in patients with Alzheimer’s disease (AD), Parkinson’s disease (PD), and schizophrenia (SZ) using Optical Coherence Tomography (OCT). The primary objective was to determine whether these neurodegenerative diseases manifest in measurable retinal changes and to assess the impact of disease duration, medication use, and cognitive decline on these alterations. A cross-sectional observational design was employed, including 132 patients and age- and gender-matched controls. OCT imaging was performed using the Topcon 3D OCT-1 Maestro 2, focusing on the retinal nerve fibre layer (RNFL), ganglion cell complex (GCC), and macular thickness. Significant retinal thinning was observed in the AD and PD groups, correlating with disease severity and cognitive decline, and was more pronounced with longer disease duration. In contrast, no significant retinal changes were identified in the SZ group. The study also explored the effects of different drug classes, revealing correlations between specific medications and retinal parameters, particularly in the AD and PD cohorts. To our knowledge, this is the first study of its kind conducted with Bulgarian patients. These findings suggest that OCT may serve as a non-invasive biomarker for neurodegeneration in AD and PD, though its utility in SZ remains limited. Future research should aim to standardize OCT protocols, further investigate the potential of retinal imaging in tracking neurodegenerative disease progression, and explore its integration with other neuroimaging techniques for a more comprehensive diagnostic and monitoring approach.